Wartość źródłowa akt dziekańskich z XIX wieku na przykładzie akt dziekana brzeźnickiego - Szkutnik, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2010)
Being in charge of the deanery clergy, deans kept documentation which was stored in the dean’s archive. In the following article the records of the deanery of Brzeziny (in the 19th century this deanery was in the diocese of Kujawy-Kalisz) are presented as an example of usefulness of this kind of documentation for research. The bishop’s and consistory’s documentation suffered some losses in wars so the diocese government orders included in the dean’s records allow to complete these missing parts. The dean’s records contain information on the deanery clergy, the congregation and church property in a deanery; as well as some cartographic and typonymic documentation. The dean’s correspondence includes letters from the local secular and church institutions. Taking all these facts into consideration, it must be stated that the dean’s records are of great importance to the history of a given region.